Antecedents and Consequence of the Use of Channel Power: Evidence From China Petrochemical Industry - Tian, Jing; Sun, Qianmin; Deng, Xiaoyu (Frontiers in Psychology, 2022)
Inconsistency exists in extant research on the relation of channel dependence, the relation of channel power, and channel satisfaction. This study, taking Sinopec as the research object, explores the relation between channel dependence, the use of channel power, and channel satisfaction. The results reveal that dependence symmetry plays a moderating role in the relation between channel dependence and the use of coercive power. Specifically, with the increase of dependence symmetry, the influence of channel dependence on the use of coercive power becomes weaker. The authors also find that the use of coercive power is negatively related with the dealer’s channel satisfaction. However, the relation strength is weaker than related studies in Western cultural context.